1989
DOI: 10.1111/j.1439-0507.1989.tb02296.x
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Pharmacokinetics of Itraconazole: An Overview

Abstract: Itraconazole (R 51211) is the prototype of a class of triazole antifungals characterized by a high lipophilicity. This property determines to a large extent the pharmacokinetics of itraconazole and differentiates it from the hydrophilic triazole antifungaI fl uconazole.The pharmacokinetics of itraconazole in man are characterized by a good oral absorption, an extensive tissue distribution with tissue concentrations many times higher than in plasma, a relatively long elimination half-life of about one day and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
269
1
3

Year Published

1994
1994
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 365 publications
(283 citation statements)
references
References 33 publications
10
269
1
3
Order By: Relevance
“…These results suggest an improvement of the bioavailability of itraconazole in oral solution. This is also evident when comparing our data with those provided by Heykants et al 15 and Kintzel et al 16 in allogeneic BMT patients treated with itraconazole 200 mg daily as capsules or itraconazole suspension formulations where itraconazole concentrations were extremely low.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…These results suggest an improvement of the bioavailability of itraconazole in oral solution. This is also evident when comparing our data with those provided by Heykants et al 15 and Kintzel et al 16 in allogeneic BMT patients treated with itraconazole 200 mg daily as capsules or itraconazole suspension formulations where itraconazole concentrations were extremely low.…”
Section: Discussionsupporting
confidence: 84%
“…On those days, two samples were taken: one before itraconazole intake (minimum concentration = C min ) and one 4 h later (maximum concentration = C max ), corresponding to the peak. 7 Plasma samples were assayed for ITRA and its active metabolite OH-ITRA by a reverse phase HPLC method. 10 The lower limit of quantification was 50 ng/ml.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…4) The spot for the possible active metabolite was detected after a longer sampling time than the itraconazole spot. The conversion of itraconazole to an active metabolite, hydroxy-itraconazole, has also been confirmed in humans (8,9). The antifungal titer obtained in our results suggested that the pharmacodynamic activity of the metabolite was comparable to that of itraconazole in mice as well as humans (4,13,23,31).…”
Section: Discussionsupporting
confidence: 63%
“…We currently do not have information on whether the active metabolite in mice was hydroxy-itraconazole (8,9). Further investigation including the identification of the active metabolite in mice would lead to a better understanding of the in vivo activity and serum antifungal titer of itraconazole.…”
Section: Discussionmentioning
confidence: 99%